Clinical Features and Outcome of Low and High Corticosteroids in Admitted COVID-19 Patients - Salma AlBahrani; Jaffar A. Al-Tawfiq; Arulanantham Zachariah Jebakumar; Mohammed Alghamdi; Nawaf Zakary; Mariam Seria; Abdulrahman Alrowis (Springer, 2021)
Introduction: There is no specific anti-viral therapies for 2019 Coronavirus Diseases (COVID-19) infection. Here, we compared patients receiving steroids at different dosages versus no steroids in severe and critical COVID-19 patients. Methods: We retrospectively studied COVID-19 patients who received low-dose or high-dose corticosteroid therapy compared to no steroid. Results: The study period, June-August 2020, included 169 patients with COVID-19 were included and there were 39.1% female and 60.9% male with an average age of 53.1 years. The distribution of cases was as follows: high-dose 39 (23.1%), low-dose 54 (32.0%), and no steroid 76 (45.5%). Of all the patients, Intensive Care Unit (ICU) admission was for 31 (18.3%), nine (5.3%) required intubation, and 52 (30.8%) had no comorbidities. There is no difference in the mean age between the different groups. However, those being treated with steroid were more likely to have a high sequential organ failure assessment (SOFA) score (0.37 ± 0.68, 0.36 ± 0.67 and 0.04 ± 0.34, for low-dose, high-dose steroid and no steroid groups, respectively (p = 0.001). Cox regression was not possible as the mortality rate was very low (3/169; 1.78%) and none of the multivariate methods would be possible. However, there was a significant difference in the hospital Length of stay (LOS) and the ICU LOS. Conclusion: Cox regression was not possible as the mortality rate was very low (1.78%) and none of the multivariate methods would be possible as the model will not converge. However, in t-test only, intubation was associated risk of mortality.